The Effect Of Digitalization And Reporting On The Performance Evaluation Of Agricultural Extension Workers - Musyarifah Musyarifah; Achmad Faqih; Hilmy Awalu Faizien (Pusat Publikasi Nusantara, 2026)
This study aims to analyze the effect of digitalized reporting on the performance evaluation of agricultural extension workers at the Department of Agriculture of Cirebon Regency. A quantitative explanatory research design with a survey approach was employed, involving 64 extension workers selected through purposive sampling. Data were collected using structured questionnaires measuring six dimensions of digitalized reporting, including system usability, data accessibility, data accuracy and completeness, time and labor efficiency, technical support and training, and user satisfaction, with performance evaluation as the dependent variable. Multiple linear regression analysis revealed that digitalized reporting significantly influences performance evaluation collectively, explaining 61.7 percent of its variation. Among the dimensions, system ease of use and user satisfaction showed positive and significant effects, indicating that user-friendly and widely accepted systems are crucial for effective performance assessments. In contrast, data accessibility, data accuracy and completeness, time and labor efficiency, and technical support and training did not have significant impacts, although technical support and training approached significance, suggesting potential for improvement. These findings highlight that the practical effect of digitalized reporting is mediated by user adoption and satisfaction, emphasizing the importance of human–system interaction in agricultural service delivery. Based on the results, recommendations include enhancing system usability and user satisfaction, optimizing technical support and training programs, and encouraging extension workers to improve their digital competencies. The study provides empirical evidence for policymakers and practitioners to develop effective digital performance management in the agricultural sector.